The Influence of the Discovery Learning Model on Student Learning Activities in Islamic Education Learning: Studi pada SMA Negeri 13 Padang - Syafriadi, Wedi (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning using the discovery learning model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the discovery learning model can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 58.71%, the first cycle 76.39% and in the second cycle it increased to 94.66%. Thus, the use of the discovery learning model can be used as an alternative to improve student learning outcomes in Islamic religious education learning.